2016
DOI: 10.1097/id.0000000000000483
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Keratinized Mucosa Width on the Health Status of Periimplant and Contralateral Periodontal Tissues

Abstract: Inadequate keratinized mucosa decreased cleansibility of implant sites and increased mucosal inflammation. There is a possibility that PA in implant sites caused more pronounced inflammatory response compared to contralateral tooth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 32 publications
5
53
0
9
Order By: Relevance
“…This agrees with the findings of a recent cross‐sectional comparative study in which implant sites with a KM band width of <2 mm were found to be more prone to brushing discomfort, plaque accumulation and peri‐implant soft tissue inflammation . In contrast, two recent studies failed to support the association between the absence of KM and discomfort during brushing . This is certainly an area of controversy where the patient pain threshold, brushing strength, mucosal thickness and other anatomy‐related factors may play important roles.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This agrees with the findings of a recent cross‐sectional comparative study in which implant sites with a KM band width of <2 mm were found to be more prone to brushing discomfort, plaque accumulation and peri‐implant soft tissue inflammation . In contrast, two recent studies failed to support the association between the absence of KM and discomfort during brushing . This is certainly an area of controversy where the patient pain threshold, brushing strength, mucosal thickness and other anatomy‐related factors may play important roles.…”
Section: Discussionsupporting
confidence: 87%
“…A priori statistical power analysis was performed assuming an intra‐class correlation coefficient (ICC) of 0.25, based on a previous study . The Kolmogorov‐Smirnov test was applied to assess normality between the parameters KM and KT.…”
Section: Methodsmentioning
confidence: 99%
“…observed that implant sites with a KM of <2 mm had significantly higher plaque and BOP scores and were associated with an increased brushing discomfort than implant sites with a KM of ≥2 mm . This finding was also supported by data from another cross‐sectional analysis (n = 60 patients) indicating that implants with a KM of <2 mm revealed a significantly higher levels of plaque accumulation as well as increased BOP+ and PD values when compared with implant sites with a KM of ≥2 mm . Canullo et al.…”
Section: Observations and Discussionmentioning
confidence: 64%
“…Although disagreement exists in the literature, the majority of studies agreed that the absence or lack (<2 mm) of KM was more likely to be associated with increased plaque accumulation, tissue inflammation, recession, attachment loss and reduced quality of self‐performed oral hygiene measures (Gobbato, Avila‐Ortiz, Sohrabi, Wang, & Karimbux, ; Lin et al, ; Ueno et al, ). These findings suggest that the presence of KM should be important not only for maintaining peri‐implant health, but also during surgical therapy of peri‐implantitis and long‐term maintenance.…”
Section: Introductionmentioning
confidence: 99%